2016
DOI: 10.1097/id.0000000000000428
|View full text |Cite
|
Sign up to set email alerts
|

Successful Surgical Protocols in the Treatment of Peri-Implantitis

Abstract: The current review failed to reveal any correlation between any particular method for SDC or defect treatment protocol and positive clinical outcomes. Further comparative studies are warranted to determine the most appropriate approach for both of these topics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 57 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, the narrative review of Froum et al. () reported that the removal of the prosthetic suprastructure in suitable cases may facilitate surgical access to the implant surface.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the narrative review of Froum et al. () reported that the removal of the prosthetic suprastructure in suitable cases may facilitate surgical access to the implant surface.…”
Section: Discussionmentioning
confidence: 99%
“…A failure rate of approximately 60% of cases treated surgically for peri-implantitis has been reported (de Waal, Raghoebar, Meijer, Winkel, & van Winkelhoff, 2016). Other studies have reported successful outcome by surgical debridement methods (Froum et al, 2016), or reconstructive surgical treatment of peri-implantitis (Ramanauskaite, Daugela, & Juodzbalys, 2016). Several studies have used combinations of grafts and barrier membranes (Aghazadeh, Persson, & Renvert,2012;Khoury & Buchmann, 2001; Roos-Jansåker, Renvert, Lindahl, & Renvert, 2007;Schwarz, Hegewald, Sahm, & Becker, 2014;Schwarz, Sahm, Bieling, & Becker, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Non-surgical treatment options may not effectively allow debridement of titanium dental implants (Froum et al, 2016;Heitz-Mayfield et al, 2018;Papathanasiou, Finkelman, Hanley, & Parashis, 2016;Renvert, Widén, & Persson, 2017;Schwarz, Becker, & Renvert, 2015). In a recent systematic review, the conclusion was that nonsurgical debridement approach was effective in the treatment of implant mucositis, but not predictable in the treatment of periimplantitis (Suárez-López Del Amo, Yu, & Wang, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Non‐surgical therapy appears to be ineffective in reducing probing depths and eliminating bacteria from implant surfaces especially in more severe cases (Persson, Samuelsson, Lindahl, & Renvert, 2010; Renvert, Hirooka, Polyzois, Kelekis‐Cholakis, & Wang, 2019). Surgical therapy has proven to be more effective in the reduction of probing pocket depths and bleeding on probing as well as in promoting new bone fill, possibly because it provides access to the defect area for removal of the granulation tissue and debridement/decontamination of the exposed implant threads (Berglundh, Wennstrom, & Lindhe, 2018; Froum et al., 2016; Sarmiento, Norton, Korostoff, Ko, & Fiorellini, 2018). The addition of bone substitutes with or without barrier membranes has demonstrated promising results in terms of radiographic defect reduction and improvement of clinical parameters, especially in well‐contained (4‐wall and 3‐wall) intrabony defects (Jepsen et al., 2016; Renvert, Roos‐Jansaker, & Persson, 2018; Roos‐Jansaker, Persson, Lindahl, & Renvert, 2014; Schwarz, Sahm, Bieling, & Becker, 2009; Schwarz, Sahm, Schwarz, & Becker, 2010; Wiltfang et al., 2012).…”
Section: Introductionmentioning
confidence: 99%